Does Public Service Motivation Affect Teacher Satisfaction From the Perspective of Urban and Rural Dual Structure? Empirical Analysis Based on Estonia TALIS 2018 Data - Jiang, Xiaodi (Frontiers in Psychiatry, 2022)
In recent years, basic education in Estonia has achieved balanced development despite the imbalance of structure and regional factors, this phenomenon has made Estonian educational system a general interest of international scholars. Based on the data from the 2018 Teacher Teaching International Survey (TALIS) database, this research divides 3004 respondents in Estonia into rural teachers and urban teachers and explores the impact of public service motivation on teacher satisfaction from the perspective of urban-rural dual structure through the grouping and comparison of ordered regression models. The study finds that the three dimensions of public service motivations in Estonia will positively affect teacher satisfaction and the influence coefficient of public service commitment and the tendency to participate in education policies on teacher satisfaction is higher in rural areas than in urban areas. In addition, the satisfaction of rural teachers in Estonia will decrease with the age of teachers and male teachers are significantly lower than female teachers, while the satisfaction of urban teachers will decrease with the improvement of academic qualifications. In terms of the implications, on the one hand, Estonia’s education policy attempts to solve the imbalance between the regional and teacher structure through subsidies and incentives; on the other hand, it uses measures such as multi-dimensional evaluation, multi-channel feedback, and local democratization to increase the teacher’s participant as well as their satisfaction.